Viburnum opulus fruit extract-capped gold nanoparticles attenuated oxidative stress and acute inflammation in carrageenan-induced paw edema model. Issue 2 (3rd April 2022) - Bidian, Cristina; Filip, Gabriela Adriana; David, Luminița; Moldovan, Bianca; Baldea, Ioana; Olteanu, Diana; Filip, Mara; Bolfa, Pompei; Potara, Monica; Toader, Alina Mihaela; Clichici, Simona
ABSTRACT: This study designed, characterized, and investigated the antioxidant and anti-inflammatory effects of gold nanoparticles coated with Viburnum opulus extract (AuNP-VO) compared to those of Viburnum opulus fruit extract (VO) and indomethacin, on experimental inflammation in Wistar rats. The structure and properties of the synthesized AuNPs-VO were evaluated by UV-Vis spectroscopy, transmission electron microscopy (TEM), dynamic light scattering (DLS), and zeta potential measurements. Their biological effects on paw inflammation were assessed at 2, 24, and 48 h after the administration of plantar carageenan by quantifying oxidative stress and inflammation and by histopathological analysis. TEM micrographs confirmed the spherical shape, homogeneous distribution, and nano-size of 65 nm. AuNP-VO and VO showed antioxidant and anti-inflammatory effects on plantar inflammation with different dynamics of action. AuNP-VO exerted antioxidant effects, especially, at 48 h and diminished the plantar inflammation in the early stages (IL-1α, IL-1β, IL-6, TNF-α and IL-10) and late stages (IL-1β, p  < 0.01) whereas VO reduced the inflammatory response, predominantly in the early stages ( p  < 0.01; p  < 0.001), and maintained reduced IL-1β values ( p  < 0.001) and a lower histopathological inflammatory score at 48 h. In conclusion, AuNP-VO and VO extract can be used as valuable agents for the treatment of diseases associated with inflammation. GRAPHICAL ABSTRACT: UF0001